"This is a piece of coral received from captain Bob": meanings and functions of tourist souvenirs. Issue 1 (2014) - Alain Decrop; Julie Masset
<x xml:space="preserve"> Abstract </x> Purpose – Tourists' special possessions are under‐studied in consumer research despite their importance in self‐identity development. Furthermore, extant studies about tourist souvenirs fail in providing an extensive and in‐depth view of souvenirs, and in exploring both their functional and symbolic dimensions. This paper aims to better and deeply understand the symbols and meanings attached to tourist souvenirs as well as the functions they fulfil in contemporary consumption. Design/methodology/approach – A naturalistic interpretive approach has been privileged. A total of 19 informants have been interviewed and observed at home in a triangulation perspective. Interview transcripts, field notes, and pictorial material were analyzed and interpreted through the grounded theory approach. Findings – A new typology of four types of symbolic souvenirs including touristic trinkets, destination stereotypes, paper mementoes, and picked‐up objects is developed. The typology is grounded on four major functions souvenirs may fulfil in terms of meanings and identity construction, that is: categorization, self‐expression, connectedness, and self‐creation. Originality/value – This study contributes to a better knowledge of tourist souvenirs, which is a typical case of consumers' special possessions that may be central in self‐identity processes. Considered as powerful "messengers of meaning", tourist souvenirs help consumers to maintain material links with cherished past experiences and to convey individual and cultural meanings to their broader existence. Typologies such as the one developed in this paper are crucial not only for researchers but also for marketers and retailers. <ack> <x xml:space="preserve"> Acknowledgements </x> Received 1 August 2013 Revised 1 August 2013 Accepted 3 November 2013 </ack>